DHARM
48 MATHEMATICAL FOUNDATION OF COMPUTER SCIENCE
- If bn = knan, where k is any arbitrary constant then corresponding generating func-
tion is B(z) = A(kz) = 1/(1 – kz). Since numeric function bn is expressed in infinite
series as
a 0 + k.a 1 z + k^2 a 2 z^2 + ................... + kn anzn + ......
= a 0 + a 1 (kz) + a 2 (kz)^2 + ................... + an (kz)n + ......
Therefore, generating function B(z) = A(kz) = 1/(1 – kz). - Since A(z) is the generating function of function an so generating function of SI an will
be zI A(z), for any positive integer I. For example, let generating function B(z) =
z^8 /(1 – 3z) then it can be written as,
B(z) = z^8. 1/(1 – 3z) ≡ zI A(z)
Then its corresponding numeric function will be S^8 an where an is the numeric func-
tion for the function 1/(1 – 3z) that is equal to 3n.
Therefore, we obtain numeric function S^8 3 n, i.e.,
S
for 0
for
8
(^38)
07
38
n
n
n
n
≤≤
≥
R
S
T
−
- Likewise, generating function for the numeric function S–I an for any integer I, will
be
z–I [A(z) – a 0 – a 1 z – a 2 z^2 – ........ – aI–1 zI–1]
Since A(z) = a 0 + a 1 z + a 2 z^2 + ........ + aI–1 zI–1 + aI zI ....... + an zn + ....
or, A(z) – a 0 – a 1 z – a 2 z^2 – ........ – aI–1 zI–1 = aI zI + aI+1 zI+1 + ..... + an zn + ....
Multiplied both side by z–I, hence we obtain
z–I [A(z) – a 0 – a 1 z – a 2 z^2 – ........ – aI–1 zI–1] = aI + aI+1 z + ..... + an zn–I + ....
= an+I zn for n ≥ 0
That is equivalent to S–I an.
For example, let an = 3n+5 for n ≥ 0 which is equivalent to numeric function S–5.3n and its
corresponding generating function can be computed by using the expression,
A(z) = z–I [A(z) – a 0 – a 1 z – a 2 z^2 – ........ – aI–1 zI–1]
i.e., A(z) = z–5 [1/(1 – 3z) – 3^0 – 3^1 z – 3^2 z^2 – 3^3 z^3 – 3^4 z^4 ]
= z–5 [3^5 .z^5 /(1 – 3z)] = 3^5 /(1 – 3z).
Example 2.30 Find the generating function for the numeric function an such that
a
0 for 0 n 5
1forn6
2forn7
3forn8
4forn9
0 for n 10
n=
≤≤
=
=
=
=
≥
R
S
|
||
T
|
|
|
Sol. Let A(z) is the generating function for an where,
A(z) = a 0 + a 1 z + a 2 z^2 + ........ + an zn + ....
Since values of a 0 to a 5 and a 10 onwards are equal to zero. So
A(z) = a 6 z^6 + a 7 z^7 + a 8 z^8 + a 9 z^9 + a 10 z^10
= 1.z^6 + 2.z^7 + 3.z^8 + 4.z^9 + 0.z^10
= z^6 .(1 + 2z + 3z^2 + 4z^3 )